Taylor’s University Graduate Research Symposium 2021 - Chong, Pei Pei; Farhadi, Ali; Chantasart, Doungdaw; Mah, Siau Hui; Sellappans, Renukha; Wong, Eng Hwa; Behbahani, Abbas Behzad; Safari, Arash; Kalantari, Tahereh; Suksiriworapong , Jiraphong; Luangmonkong, Theerut; Suriyaphan, Orasa (Life Sciences, Medicine and Biomedicine, 2022)
Graduate Research Symposium 2021 (GRS2021) was held virtually via Zoom on the 30th of November 2021. The theme of the symposium was Scientific Research Today: Borderless, Collaborative and Innovative. The symposium aimed to highlight the various types of scientific research being conducted by postgraduates from different international and local institutions to expand participants’ field of knowledge as well as encourage networking. GRS2021 covers a wide range of topics, which include natural products, drug discovery and formulation, life sciences, pharmaceutical sciences, medical sciences, food sciences and technology. This special issue exhibits the latest research findings by postgraduates from various scientific background. The emphasis is on studies that will contribute to the current knowledge and understanding in the targeted field of study.